KOREAN CULTURAL PHENOMENON ON COMMUNICATION PATTERNS AND BEHAVIOR OF UINSU COMMUNICATION SCIENCE STUDENTS AGED 18-25 YEARS - Siregar, Karin Reindra Phasya; Nuzrul Ikhwanusshofa; Salsabila Fazri Az-zahra (OPINI: Journal of Communication and Social Science, 2024)
Korean culture has penetrated the world, including Indonesia, through the Korean Wave (Hallyu) phenomenon which includes K-Pop, K-Drama, Culinary and Fashion. This phenomenon has a big influence on teenagers aged 18-25 years in Indonesia, who are in an important phase of identity formation and are very vulnerable to external influences. Through social media and other platforms, teenagers are adopting Korean language and communication styles. Research shows a correlation between consumption of Korean cultural content and changes in teenagers' behavior and communication patterns. Qualitative research methods were used, with in-depth interviews and literature review as the main approaches. Interviews were conducted with UINSU students aged 18-25 years who are interested in Korean culture to understand its impact on their communication patterns. The results showed that adolescents learn through observation and imitation of Korean content, which strengthens their communication and behavior patterns. However, the influence of Korean culture has not changed their view of Indonesian culture, which they still appreciate and love. This research reveals that although Korean culture has a significant influence, Indonesian teenagers are able to balance between enjoying foreign culture and maintaining their local cultural identity.